PENGUATAN NILAI BUDAYA BUTON : Tradisi Adat Pisombo Kampung Kayu Merah Fakfak - Ode, Wa Seni; La Muhamad, Idul; Renyaan, Kasman (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2025)
This article elaborates on the strengthening of Buton cultural values through the Pisombo customary tradition in Kampung Kayu Merah, Fakfak, West Papua. The study aims to uncover and explain the forms of reinforcement of Buton cultural values inherited through the implementation of the Pisombo tradition, as well as to analyze this ritual in strengthening the identity and social cohesion of the Buton community in Fakfak. The research employs an ethnographic method with data collection techniques including observation, in-depth interviews, documentation, and Focus Group Discussions involving customary masters, community leaders, and the girls who are the main participants in the ritual process. A literature study was also conducted to trace various written sources related to the practice of Pisombo within the cultural heritage of Buton. The collected data were analyzed and interpreted to uncover the meanings and values contained in the tradition and then presented in the form of an ethnographic narrative. The results indicate that Pisombo is a rite of passage marking the transition of adolescent girls to adulthood, signified by their first menstruation. Pisombo functions as a space for cultural education, a mechanism of social control, and a means of transmitting values such as courtesy, personal purity, family responsibility, and community solidarity. Within the life of the Buton community in Fakfak, this tradition serves as an internal mechanism that maintains social cohesion and ensures the sustainable regeneration of Buton cultural values. These findings confirm that the Pisombo customary tradition remains relevant as a strategy for strengthening the identity and cultural resilience of the Buton community in the multiethnic city of Fakfak, which is open and highly respects cultural and religious diversity, in accordance with the life philosophy of “One Stove, Three Stones.”